Nutritional and Functional Properties of Novel Protein Sources - Can Karaca, Asli; Nickerson, Michael; Caggia, Cinzia; Randazzo, Cinzia L.; Balange, Amjad K.; Carrillo, Celia; Gallego, Marta; Sharifi-Rad, Javad; Kamiloglu, Senem; Capanoglu, Esra (Informa UK Limited, 2022)
There has been a growing demand towards alternative protein sources due to population growth and increasing consumer awareness on sustainability and environmental issues. Proteins from various plant, marine, insect and microbial sources are considered as excellent alternatives to substitute traditional animal-based proteins due their relatively low cost, sustainable production and nutritional value. This work is an overview of the physicochemical properties, functionality and nutritional quality of novel protein sources. Current information on the proximate composition, amino acid profile, digestibility, physicochemical and functional properties is presented. Effects of extraction method applied for obtaining protein ingredients from novel sources on protein composition, functionality and nutritional quality are discussed. Findings of some of the recent studies focusing on modification of protein structure and improvement of functionality are reviewed. Potential end product applications and challenges related to the production and use of protein ingredients obtained from novel sources are discussed. Furthermore, future research recommendations are presented.
Keywords: legumes; insect proteins; Cereals; marine plant proteins; seeds; microbial derived proteins